Enhancing Functional Symmetry in Football Athletes Through Corrective Exercise Interventions - Himmat Eshboyev; Aiman Zhakupova (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: One system used in identifying athletes with a high risk of experiencing sports related physical injuries is Functional Movement Screen. In considering the screening of movement patterns, the FMS readily identifies functional limitations and asymmetries. This research sought to determine if FMS composite score can mitigate asymmetrical problems among football athletes when corrective exercise program is introduced and used. Methodology: Thirty-three football players of Benguet State University divided into exercise and control groups with the former subjected to a corrective exercise program to find out if there is a significant reduction of asymmetry problems among the athletes in the post-test. The level of significance was set at α = .05. Main Findings: Results revealed that the athletes in the exercise group reduced their asymmetrical problems significantly compared to those who belong to the control group. Novelty/Originality of this study: With this finding, it can then be concluded that with the use of corrective exercise programs, asymmetrical problems can be improved among athletes.